2019
DOI: 10.2196/15023
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Patients’ Intentions to Use Diabetes Management Apps Based on an Extended Unified Theory of Acceptance and Use of Technology Model: Web-Based Survey

Abstract: Background Diabetes poses heavy social and economic burdens worldwide. Diabetes management apps show great potential for diabetes self-management. However, the adoption of diabetes management apps by diabetes patients is poor. The factors influencing patients’ intention to use these apps are unclear. Understanding the patients’ behavioral intention is necessary to support the development and promotion of diabetes app use. Objective This study aimed to i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
140
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(192 citation statements)
references
References 82 publications
17
140
2
1
Order By: Relevance
“…The positive impact of effort expectancy on behavioural intention is supported by other studies that analysed consumer usage of health informatics [25]. However, the impact of effort expectancy on behavioural intention is more prominent for older users as a study with younger and well-educated users found that this relationship was not significant [25]. Therefore, diabetes applications should be designed so that they are easy to use and understand, especially for older users.…”
Section: Effort Expectancymentioning
confidence: 78%
See 3 more Smart Citations
“…The positive impact of effort expectancy on behavioural intention is supported by other studies that analysed consumer usage of health informatics [25]. However, the impact of effort expectancy on behavioural intention is more prominent for older users as a study with younger and well-educated users found that this relationship was not significant [25]. Therefore, diabetes applications should be designed so that they are easy to use and understand, especially for older users.…”
Section: Effort Expectancymentioning
confidence: 78%
“…For patients aged 50 years or older, effort expectancy was identified as a key factor for diabetes applications [24]. The positive impact of effort expectancy on behavioural intention is supported by other studies that analysed consumer usage of health informatics [25]. However, the impact of effort expectancy on behavioural intention is more prominent for older users as a study with younger and well-educated users found that this relationship was not significant [25].…”
Section: Effort Expectancymentioning
confidence: 85%
See 2 more Smart Citations
“…While theoretical models of technology adoption (51) are one step towards understanding factors that in uence (mobile) technology adoption and use, there is a gap in proving both signi cant and substantive usage effects for mHealth (52,53). Previous studies investigated factors in uencing mHealth use in speci c target groups (e.g., 54,55), for speci c diseases or health topics (56)(57)(58)(59)(60), and for sustained mHealth engagement (61). This study aims to explicate the effect of social support.…”
Section: Social Support and Technology-supported Diabetes Self-managementioning
confidence: 99%